Exploring the prospect of intrinsic wave propagation in evaluating myocardial stiffness among patients with type 2 diabetes - Cheng, Qiao; Huang, Xiao; Fan, Xinying; Sun, Jie; Zhang, Jun; Tang, Qiaoying; Deng, Youbin; Bi, Xiaojun (Frontiers in Cardiovascular Medicine, 2023)
Background Diabetes predisposes affected individuals to impaired myocardial perfusion and ischemia, leading to cardiac dysfunction. Increased myocardial stiffness is an independent and significant risk factor in diastolic dysfunction. This study sought to estimate myocardial stiffness in Type 2 diabetes (T2DM) patients using the intrinsic wave velocity propagation (IVP) along the longitudinal wall motion during late diastole and evaluate the value of IVP in assessing cardiac function and structure. Methods 87 and 53 participants with and without T2DM (control group) were enrolled. Of the 87 T2DM patients (DM group), 43 were complicated with hypertension (DM + H group), and 44 were not (DM-H group). Ultrasound parameters were measured and analyzed, including color M-mode flow propagation velocity, global longitudinal systolic strain (GLS), and IVP. Results IVP was higher in the DM group than in the control group (1.62 ± 0.25 m/s and 1.40 ± 0.19 m/s, P < 0.001). After stratification for hypertension, IVP in both DM + H (1.71 ± 0.25 m/s) and DM-H (1.53 ± 0.20 m/s) groups were found to be significantly higher than that in the control group (1.40 ± 0.19 m/s); also, the difference of IVP between DM + H and DM-H group reached statistical significance. Moreover, IVP was significantly correlated with flow propagation velocity during early diastole (Pve) (r = −0.580, P < 0.001), flow propagation velocity during late diastole (Pva) (r = 0.271, P < 0.001), GLS (r = 0.330, P < 0.001), interventricular septal thickness at end-diastole (IVSd) (r = 0.321, P < 0.001), blood glucose (r = 0.246, P < 0.003), systolic blood pressure (r = 0.370, P < 0.001) and diastolic blood pressure (r = 0.389, P < 0.001). Conclusions The results indicated the application potential of IVP in assessing the early detection of cardiac function changes noninvasively and sensitively. The correlation with myocardial stiffness warrants further studies to substantiate its potential clinical utility.